‎The impact of applying international standards for professional project management on the quality of projects: an applied study on the projects of the Ministry of Health in Makkah Al-Mukarramah - Al-Zahrani, Fahd Mohammed Ahmed; Al-Madani, Nadin Fahad (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the impact of applying international standards for professional project management on the quality of projects, through an applied study on the projects of the Ministry of Health in Makkah Al-Mukarramah. The researcher used the descriptive analytical approach. He also used the questionnaire as the main tool for collecting data from the study sample. The study sample consisted of a random sample of (100) employees working in the projects of the Ministry of Health in Makkah Al-Mukarramah. The study reached several results, the most important of which is: There is a high degree of application of international standards for professional project management in the projects of the Ministry of Health in Makkah Al-Mukarramah. There is a high level of quality for the projects of the Ministry of Health in Makkah Al-Mukarramah. There is a statistically significant correlation between the application of complete professional project management standards represented in (management of scope and integration of projects, management of project time and cost, management of project purchases and resources, management of project communications, management of project risks, management of project stakeholders) and the quality of projects, as the application of these Standards contribute to increasing the quality of projects of the Ministry of Health in Makkah Al-Mukarramah. The study recommended several recommendations, including: strengthening the early warning systems in place at the Ministry of Health with the aim of reporting risks that may face the implementation of future projects. Ensure follow-up of feedback reports related to project activities from supporting agencies. paying attention to commitment to teamwork and team spirit in order to achieve the desired strategic goals.
Keywords: Project management; international standards for professional project management; project quality; Saudi Ministry of Health; projects of the Ministry of Health in Makkah Al-Mukarramah